Diamondback Moth, Plutella xylostella (L.), (Lepidoptera: Plutellidae ), and Other Insects of Canola, Brassica napus L., in Gauteng Province, South Africa - Mosiane, M S (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2002)
Canola, Brassics napus L. is a relatively new crop in South Africa. Insect pests have not yet been a major problem, but the notorious brassica specialist, diamondback moth (DBM), Plutella xylostella (L.) (Plutellidae) is establishing itself as a serious pest of this crop. DBM is the most important insect pest of plants from the family Brassicaceae throughout the world. It has developed resistance to all chemical pesticides used against it in the field and to toxins of the bacterium Bacillus thuringiensis. The pest status of DBM in South Africa is lower than in other countries with similar climates. However, due to indiscriminate use of pesticides, local populations of DBM are showing signs of resistance. An initial survey has indicated that in addition to DBM, canola is also attacked by aphids, Myzus persicae (Sulzer), Brevicoryne brassicae (L.), Lipaphis e1ysimi (Kaltenbach), (Aphiade), thrips, Thrips tabaci (Lindeman) and other pests mostly brassica specialists. The study was initiated to determine the composition of the community of insects found on canola, the seasonal phenology of DBM populations in canola, and the composition, relative abundance and seasonality of its parasitoids. Monitoring of the insects was carried out at weekly intervals for three years at Rietondale and Bapsfontein in Gauteng province of South Africa. Berlese funnels have been found to be useful in extracting insects from plants, and were used to indicate the presence ofDBM larvae and other insects found on canola. Adults of DBM were monitored with synthetic pheromone traps; larval and pupal populations were monitored by scouting canola plants. Samples of larvae, pupae and parasitoid cocoons were brought into the laboratory. Parasitoids that emerged were identified and their incidence recorded. Monolepta cf bifasciata (Chrysomelidae) and Listroderes costrirostris (Schoener) (Curculionidae) were the most abundant of the coleopteran pests. (DBM) and Heliothis armigera (H.) (Noctuidae) were most abundant lepidopteran pests of Canola. There was a high proportion of first and second instar larvae as indicated by the results of the Berlese funnels as compared to visual scouting in Bapsfontein. From May to August the infestation level of DBM was high, reaching the maximum of 0.25 larvae per plant in June 1996, then declined and remained low for the rest of the season in Rietondale. From September to December for all three years of the study, the population levels Of DBM were high, reaching a maximum of 9.6larvae per plant in September 1997, and remained low from January to August in Bapsfontein. The number of adult moths per trap per week ranged from 0 to 91 in Rietondale, peaking in January 1996 and September 1997. There was no correlation between infestation levels and the pheromone trap catches. In contrast to Rietondale, there was a high correlation between pheromone trap catches and subsequent larval infestations at Bapsfontein. Although DBM infestation levels were generally low, parasitism levels often reached 100% caused by a complex of parasitoids. During the period of study, the following hymenopteran parasitoids were recorded: Cotesia plutellae (Kurdjumov) and Apanteles eriophyes (Nixon), Braconidae), both larval parasitoids, Diadegma mollipla (Holmgren) (Ichneumonidae), and Oomyzus sokolowskii (Kurdjumov) (Eulophidae), larval-pupal parasitoids, Diadromus collaris (Gravenhorst) (Ichneumonidae) pupal parasitoid, and the hyperparasitoids Mesochorus sp. (Ichneumonidae) and Pteromalus sp. (Pteromalidae). Cotesia plutellae was the most abundant parasitoid occurring throughout the year..
Keywords: Plutellidae; Plutellidae -- South Africa -- Gauteng; Rape (Plant) -- South Africa -- Gauteng; Canola; Plant parasites